Integrating Information Technology and Stem Learning Models in Industrial 4.0 Revolution - Handayani, Sri; Mintarti W, Sri Umi; Megasari, Rizza; Kustiandi, Januar (KnE Social Sciences, 2020)
At present the world is entering the era of industrial revolution 4.0 which is closely related to information technology on the basis of human life (Kemenristekdikti, 2018a). With these changes, of course the world of education must also immediately respond to these changes. The steps that can be taken is by integrating information technology with innovative learning models. As a teacher in the Indonesian era 4.0 gave birth to a term known as Teacher 4.0 Challenges & Requirements. To become a 4.0 teacher must have 3 components, namely: 1) Human - Based & Didactical Challengee; 2) Organizational Challengee and 3) Technological Challengee. (Abdelrazeq, 2016). To support these competencies, one of the learning models that can be used is the STEM-based learning model. STEM Education is a combination of areas of Science, Technology, Engineering, and Mathematics (STEM) (Duran, et al., 2016). This paper aims to: 1) explain the perception of information technology and STEM learning for prospective economic teachers. 2) describes the efforts to integrate Information Technology and STEM-based Learning Models in the face of the Age of Industrial Revolution 4.0. Keywords: Industrial Revolution Era 4.0, Information Technology, and Innovative Learning Models, STEM, Teacher Competencies 4.0.